Strategi Peningkatan Kualitas Layanan Digital dalam Perspektif Public Value Studi pada Website PLAVON Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo - Rizky Dwi Sulistyo Rahayu; Fitrotun Niswah; Meirinawati Meirinawati; Eva Hany Fanida (Studi Administrasi Publik dan ilmu Komunikasi, 2026)
The implementation of e-government in government administration can make services more efficient, transparent, and reliable, as well as provide faster service to the public. The Sidoarjo Regency Population and Civil Registration Office launched the PLAVON website as a digital service. This study aims to describe the strategy for improving digital service quality from a public value perspective, focusing on the PLAVON website of the Sidoarjo Regency Population and Civil Registration Office. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the quality of PLAVON’s digital services can be analyzed through three dimensions of public value: improved public service, improved administration, and improved social value. In the improved public service dimension, PLAVON enhances the ease and speed of population administration services; however, these improvements are still constrained by technical system disruptions and unstable website performance. In terms of improved administration, the implementation of digital services through PLAVON contributes to greater transparency and improved employee professionalism. Meanwhile, within the improved social value dimension, PLAVON plays a role in strengthening public trust in government institutions. This study emphasizes that the improvement of digital service quality is not solely dependent on technical factors but also on the government’s capacity to generate tangible and sustainable public value for the community.